Age estimates of Frullania (Frullaniaceae, Porellales) main lineages: another example of rapid and recent diversification in liverwort evolution. Issue 2 (4th March 2017) - Silva, Sara E.; Silva, Diogo N.; Almeida, Tereza; Garcia, CÉsar A.; Paulo, OctÁvio S.; Sim-sim, Manuela
Abstract : Frullania Raddi is an extant genus of liverworts (Bryophytes) widespread around the world. It belongs to the family Frullaniaceae Lorch., with a large number of species distributed into several subgenera, sections and subsections according with different morphological classifications. As shown in previous studies, most Frullania sub-generic classifications are supported by molecular data, indicating that morphological characters appear well suitable to discriminate species. However, deep among-clade relationships remain unclear, probably due to the rapid diversification of main clades, paralleling other plant lineages. In this study, we reconstruct Frullania phylogeny based on available molecular data used in previous studies, and we present time estimates for the origin of its main branches. Results supported the monophyly of most subgenera as demonstrated in previous studies and supported a rapid diversification of these main lineages. Time estimates under a relaxed molecular clock and with integrated fossil evidence and nucleotide mutation rates further suggested a Jurassic origin of the genus and a rapid diversification during Palaeogene and Neogene. This may have been influenced by geographical and climate changes during these periods as predicted for most leafy liverworts.